A constituição do sujeito celebridade no site ego: (re)configurações da intimidade em tempos de hiperexposição midiática - Silva, Francisco Vieira da (2016)
This thesis analyzes how the website Ego presents the intimacy of the celebrity subject. For this, we are based on the theoretical reflections engendered in the scope of Discourse Analysis, especially on the resonances from the lucubration of Michael Foucault for this theoretical dimension. By conceiving that the notion of intimacy is set in the continuous slide of historical discontinuities, we aim, from a genealogical perspective, to investigate the conditions of possibility that contribute to the (re)configuration of this notion along the time, assuming other modes of existence. We add to this observation the mutant constitution of subjects who, along the history, were tied to fame, glory and stardom. When we associate these two assertive, we see modifications in how the discourse about the celebrity subject’s intimacy is constructed, in the media spaces, more precisely in the actual web features, which influence the ample proliferation of discourses around the intimate life. The advent of a more collaborative web in convergence with other media sustained the irruption of possibilities in which the subject can be seen in the interior of the digital network. In this sense, the choice of the corpus for this thesis, formed by 38 (thirty eight) news from Ego website, was anchored in these ascertainments about the rhizomatic character of web, which was intensified, especially, by the popularization of social interconnection networks. In order to organize the inevitable dispersion of discourses about the intimacy of the famous subject in the limits of the focused website, we consider the following thematic path: sexuality, family and love. Despite we, sometimes, exceed the limits of this path, it was precise in the process of immersion and entanglement of the sparse wires that form the discursive weaving of the statements published in the Ego website. In synthesis, the analysis allowed us to observe the functioning of a certain subject position in the production of news disseminated by Ego. This position is based on the use of discursive strategies mobilized by the subject author of the news, in which some sense effects are registered. We can emphasize, among these strategies, the use of celebrities’ direct discourse, aiming to produce sensational confessions of intimate life, published by such subjects in various web spaces; the crop undertaken by this position that is enunciated in Ego, related to the voice, in direct discourse, of celebrities, indicating certain argumentative directions and, finally, the treatment given to celebrity, specially marked by a particular familiarity in the use of determined forms of referring to the celebrity subject, or even in relation to insinuations about the famous’ particularities, allow us to conclude that the journalist subject do not only inform, a function commonly spread by discourses about a certain journalistic impartiality, but also orients senses about how the celebrity subject is constructed in the context of digital media.